The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1976
DOI: 10.1111/j.1651-2227.1976.tb04887.x
|View full text |Cite
|
Sign up to set email alerts
|

THE AETIOLOGY OF OBESITY IN CHILDREN A Study of 101 Twin Pairs

Abstract: The aetiology of obesity in children is studied here with the aid of a material consisting of 40 monozygotic and 61 dizygotic twins. The importance of heredity, early nutrition, and environment during preschool age is analysed. Genetic factors, studied by comparison of intra-pair differences in monozygotic and dizygotic twins, apparently play a decisive role in the origin of obesity. Analysis of the relation between birth weight and later development of subcutaneous fat in different types of twins does not sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
3

Year Published

1977
1977
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(55 citation statements)
references
References 13 publications
2
50
0
3
Order By: Relevance
“…The Hereditary Abilities Study initiated in 1952 was a comprehensive study performed in the United States to investigate heritability of physical traits, including measures of adiposity (birth weight, body weight, and waist circumference) among monozygous and dizygous twins, which demonstrated that the greater part of variance for these traits was genetically determined (Clark 1956). These findings were consistent with other studies reported over 20 years later indicating a high heritability of body weight among monozygous and dizygous twins (Brook et al 1975;Borjeson 1976;Feinleib et al 1977). However, it became apparent that genetic susceptibility interacts with undefined environmental factors to increase adiposity and body weight, in what has formally become known as a ''gene-environment interaction'' and defined as Fig.…”
Section: Heritability Of Body Weight and Interaction With Environmentsupporting
confidence: 91%
See 1 more Smart Citation
“…The Hereditary Abilities Study initiated in 1952 was a comprehensive study performed in the United States to investigate heritability of physical traits, including measures of adiposity (birth weight, body weight, and waist circumference) among monozygous and dizygous twins, which demonstrated that the greater part of variance for these traits was genetically determined (Clark 1956). These findings were consistent with other studies reported over 20 years later indicating a high heritability of body weight among monozygous and dizygous twins (Brook et al 1975;Borjeson 1976;Feinleib et al 1977). However, it became apparent that genetic susceptibility interacts with undefined environmental factors to increase adiposity and body weight, in what has formally become known as a ''gene-environment interaction'' and defined as Fig.…”
Section: Heritability Of Body Weight and Interaction With Environmentsupporting
confidence: 91%
“…This population at one time had a subsistence lifestyle but is now predisposed to weight gain and diabetes as a result of a modern obesogenic lifestyle (Knowler et al 1983(Knowler et al , 1991. Moreover, a number of well-designed studies using both monozygotic and dizygotic twins have provided strong evidence demonstrating that children with obesity susceptibility genes living in an obesogenic environment (adopted family) are at increased risk of developing childhood obesity (Borjeson 1976;Silventoinen and Kaprio 2009;Silventoinen et al 2010). These results are consistent with recent anthropological studies verifying that geneenvironment interactions are responsible for marked differences among populations genetically susceptible to weight gain (Casazza et al 2011).…”
Section: Thrifty Gene Hypothesismentioning
confidence: 99%
“…The only other study of overweight twins analysed individual differences among overweight twins rather than analysing the difference between the overweight group and the population. 5 This is a problem because the question is not why one obese person differs slightly in weight from another obese person but rather why obese persons as a group are so much heavier than the rest of the population.…”
Section: Introductionmentioning
confidence: 99%
“…Also, studies of the heritability of skinfold thicknesses in children yield similar results. 13,18,19 Adoption studies, on the other hand, show only moderate effects of genes (30 ± 40%) on variation of BMI and skinfolds, and family studies generally yield estimates of heritability intermediate between the twin and adoption studies. 20 Results from longitudinal studies support the suggestions from cross-sectional data that there are effects of genes on BMI that are age-speci®c.…”
Section: Introductionmentioning
confidence: 99%
“…3 ± 12 Heritability seems to be higher at younger ages, at least in cross-sectional studies. 4,7,8 The few studies performed in childhood, 1,13 adolescence, 1,14,15 and young adulthood, 16,17 show heritabilities from 70% to over 90% for BMI. Also, studies of the heritability of skinfold thicknesses in children yield similar results.…”
Section: Introductionmentioning
confidence: 99%